The Measurement of Employee Performance Based on Work Stress and Workplace Conflict at BCA Finance Ltd Medan - Yoki Amriza; Husni Muharram Ritonga; Dewi Nurmasari Pane (Britain International of Humanities and Social Sciences (BIoHS) Journal, 2022)
Stress at work will cause various consequences for workers. Psychologically stress will cause a sense of job dissatisfaction with the emergence of emotional stress such as irritability, rudeness or anxiety (Warni, 2016). Conflict comes from the Latin verb "Configere" which means hitting each other. Sociologically, conflict is defined as a social process between two or more people in which one party tries to get rid of the other party by destroying it and making it powerless (Enny : 2018). Good employee performance always makes a positive contribution. In general, employee performance could be assessed from an increase in the rating or financial statements of the company. If the company experiences continuous profit, then the employee's performance is considered to make a positive contribution (Julvia: 2016). This research is at BCA Finance Ltd, Perintis Kemerdekaan street, Medan. The object of this research is all employees of BCA Finance Ltd Medan. This research was conducted from November 2021 to February 2022. Researchers get the results that work stress and workplace conflict have a significant negative effect simultaneously on employee performance. This means that if work stress and workplace conflict is reduced, employee performance would increase.